LEARNING CENTER DI BANJARBARU - Oktaviani, Tiara; Anhar, Pakhri (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
Technological advancements have significantly altered the way students learn, pushing them towards seeking more relaxed and comfortable learning environments outside educational institutions. Nowadays, students often opt for cafes as alternative study spaces, although this choice misaligns with the primary function of cafes and can disrupt patrons who are there solely for dining. The scarcity of adequate external educational facilities has led to competition for ideal study spaces. In this context, the Learning Center emerges as a solution by providing a space specifically designed to accommodate and meet students' educational needs. To achieve this, a Hybrid Architecture approach is employed, merging the functions of a study environment and a cafe. The Learning Center thus fosters an inclusive and supportive learning environment, addressing both the educational and social needs of students.